علامہ اقبال کے سفر یورپ پر جانے سے قبل اور بعد کے زاویے کا تحقیقی و تجزیاتی مطالعہ: A Research and Analytical Study of Allama Iqbal's Perspective Before and After His Journey to Europe - Aainy Syed, (Al Manhal Research Journal, 2024)
Allama Iqbal, whom the world knows as the poet of the East. You are recognized as distinguished and great among the poets of the 20th century, not only in your era but also today, in terms of your unique style of thought. Because you were not only a poet but also a great thinker, philosopher, broad-minded Islamic thinker and the founder of the idea of ​​Pakistan. Just as there are different periods of physical development in human life, in the same order, the intellectual and conscious development of man also continues. Similarly, the process of change and change in Allama Iqbal's thoughts is due to the political conditions, social conditions and western concepts of his time. The negative side which is revealed in Hawan's poetry during his travels to Europe for higher education is prominent. Accordingly, historians and analysts associate the periods of Allama Muhammad Iqbal's life with the periods of his poetry.In this article, a research and analytical study of the stages of Allama Iqbal's intellectual evolution is being presented. To understand that what fruits were obtained from the thoughts and ideas of Allama in his time and is it possible to cure the ill health of contemporary Muslims with these ideas even today?